SPE Offshore Europe Conference and Exhibition 2019
DOI: 10.2118/195765-ms
|View full text |Cite
|
Sign up to set email alerts
|

Developing Nanocomposite Gels from Biopolymers for Leakage Control in Oil and Gas Wells

Abstract: Crosslinked polymer gels have been widely used to overcome water and gas coning problem in the petroleum industry. Recently, nanoparticles are identified to have a potential of reinforcing the polymer gel systems by improving physical bonding and heat transfer properties in the gel structure. In this study, silicon dioxide and aluminium oxide nanoparticles were introduced to xanthan gum polymers that were crosslinked by chromium (III) acetate, to create polymeric nanocomposite gels with higher shear strengths.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 12 publications
0
3
0
1
Order By: Relevance
“…Figure d clearly shows that the “holes” in the gel network gradually disappear after the addition of Cr 3+ , while the “holes” in the gel reappear after the addition of LSM. Yudhowijoyo et al similarly found that the average storage modulus of the gels decreased with the addition of 1000 ppm of SiO 2 to the XC/Cr 3+ system. Kang et al suggested that the LSM adsorbed on the polymer chains and hindered the formation of multistage networks and entanglements.…”
Section: Improved Gel Performancementioning
confidence: 95%
See 1 more Smart Citation
“…Figure d clearly shows that the “holes” in the gel network gradually disappear after the addition of Cr 3+ , while the “holes” in the gel reappear after the addition of LSM. Yudhowijoyo et al similarly found that the average storage modulus of the gels decreased with the addition of 1000 ppm of SiO 2 to the XC/Cr 3+ system. Kang et al suggested that the LSM adsorbed on the polymer chains and hindered the formation of multistage networks and entanglements.…”
Section: Improved Gel Performancementioning
confidence: 95%
“…Yudhowijoyo et al 124 similarly found that the average storage modulus of the gels decreased with the addition of 1000 ppm of SiO 2 to the XC/Cr 3+ system. Kang et al 125 suggested that the LSM adsorbed on the polymer chains and hindered the formation of multistage networks and entanglements.…”
Section: Improved Gel Strengthmentioning
confidence: 95%
“…Besides, several papers claimed that the strength and thermal stability of polymer-based gels may be signicantly improved by the addition of nanoparticles. [28][29][30][31][32][33] Referring to the underlying mechanism, most of the previous studies focused on the interactions, particularly the hydrogen bonds, between the polymer chains and the nanoparticle surface. However, others argued that the weak interactions were inadequate to make such improvements.…”
Section: Introductionmentioning
confidence: 99%
“…Перед непосредственным проведением ремонта скважину необходимо заглушить. Таким образом, осложнения, возникающие при глушении скважин, являются актуальной проблемой для каждой нефтегазодобывающей компании [1,2].…”
Section: Introductionunclassified